(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we use the induced mappings to obtain some new characterizations of open fuzzy mappings in connection with closures and closed fuzzy mappings in connection with interiors of fuzzy sets. We also investigate another representation of open fuzzy and closed fuzzy mappings under surjective mappings. Furthermore, we prove that images of saturated fuzzy sets under surjective open fuzzy and closed fuzzy mappings are closed fuzzy and open fuzzy sets, respectively. We furnish illustrative examples to elucidate the displayed results.